Pemodelan Proses Bisnis Menggunakan BPMN (Business Process Model And Notation) Untuk Meningkatkan Efisiensi Operasional Dan Pelayanan Di Rafah Store : Books And Mercandise Upt Pusat Pengembangan Bisnis Uin Raden Fatah Palembang - Nando Satria; M. Syendi Apriko (Prosiding, 2025)
Rafah Store: Books and Merchandise is a business unit under the management of the UPT Business Development Center of UIN Raden Fatah Palembang, which focuses on selling books and various campus-themed merchandise products. In its operational practices, this store faces several obstacles, such as an unorganized service flow, the use of time-consuming manual procedures, and the lack of systematically documented business process documentation. This study aims to design a business process modeling at Rafah Store using the Business Process Model and Notation (BPMN) approach as an effort to improve operational efficiency and service quality. The approach used in this study is descriptive qualitative, with data collection methods through direct observation, interviews, and analysis of store operational activity documents. This study resulted in a core business process modeling that includes product ordering flow, customer service, inventory management, and financial reporting processes. BPMN is used to clearly visualize the workflow and the roles of each party involved. The application of this BPMN model allows management to more easily identify inefficient processes, speed up service times, and improve coordination between departments. In addition, this model also has the potential to become a foundation for the development of a more integrated information system in the future. Overall, BPMN has proven to be an effective tool in improving operational efficiency and service quality at Rafah Store.